2023
DOI: 10.3390/foods12142751
|View full text |Cite
|
Sign up to set email alerts
|

Food and Nutrition Literacy: Exploring the Divide between Research and Practice

Abstract: This study addresses the growing recognition of the importance of food and nutrition literacy, while highlighting the limited research in this field, particularly the gap between research and practice. A bibliometric analysis of publications on food and nutrition literacy research from the Scopus database was carried out. Endnote 20, VOSviewer, and Harzing’s Publish or Perish were used to analyze the results. The growth of publications, authorship patterns, collaboration, prolific authors, country contribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In recent years, there has been a growing focus on the concepts of food and nutrition literacy [10]. These concepts have evolved from the broader domain of health literacy, reflecting the necessity for individuals to orient themselves in the complex issues of food and nutrition through specialized knowledge and skills [41].…”
Section: Food and Nutrition Literacy: Definitions And Measuresmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent years, there has been a growing focus on the concepts of food and nutrition literacy [10]. These concepts have evolved from the broader domain of health literacy, reflecting the necessity for individuals to orient themselves in the complex issues of food and nutrition through specialized knowledge and skills [41].…”
Section: Food and Nutrition Literacy: Definitions And Measuresmentioning
confidence: 99%
“…This is amplified in rural /remote areas and those of lower socio-economic status and household income [59]. People from low-income or marginalized backgrounds may, therefore, face additional challenges in accessing nutritious foods and understanding good dietary practices, and it is necessary to address these disparities by implementing interventions specifically designed for these populations [10]. A study conducted by Eicher-Miller et al [60] demonstrated the effect of "Food Stamp Nutrition Education", a nutrition education program aimed at low-income participants.…”
Section: Relation Between Literacy and Quality Dietmentioning
confidence: 99%
See 2 more Smart Citations
“…People feel that scientists do not agree with each other and are constantly changing their minds. With so much information about what people should eat and how much exercise they should do each day, it can be difficult for even the most educated people to sort through it all, and this confusion can lead them to make unhealthy choices when they are not aware of what they are doing [1,2]. In the first part of the paper, we attempted to clarify the differences between nutrition and food literacy, which are often wrongly used as synonyms.…”
Section: Introductionmentioning
confidence: 99%